Production of CO-rich Hydrogen Gas from Methane Dry Reforming over Co/CeO2 Catalyst - Ayodele, Bamidele V.; Khan, Maksudur R.; Cheng, C. K. (Department of Chemical Engineering, Diponegoro University, 2016)
Production of CO-rich hydrogen gas from methane dry reforming was investigated over CeO 2-supported Co catalyst. The catalyst was synthesized by wet impregnation and subsequently characterized by field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDX), liquid N2 adsorption-desorption, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) for the structure, surface and thermal properties. The catalytic activity test of the Co/CeO2 was investigated between 923-1023 K under reaction conditions in a stainless steel fixed bed reactor. The composition of the products (CO and H 2) from the methane dry reforming reaction was measured by gas chromatography (GC) coupled with thermal conductivity detector (TCD). The effects of feed ratios and reaction temperatures were investigated on the catalytic activity toward product selectivity, yield, and syngas ratio. Significantly, the selectivity and yield of both H2 and CO increases with feed ratio and temperature. However, the catalyst shows higher activity towards CO selectivity. The highest H2 and CO selectivity of 19.56% and 20.95% respectively were obtained at 1023 K while the highest yield of 41.98% and 38.05% were recorded for H2 and CO under the same condition.